The Role of School-Level Subject Teacher Meetings in Improving Competence Integrated Social Teacher - Fitriah Fitriah; Elpisah Elpisah; Hartini Hartini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of MGMPS in improving teachers' pedagogical and professional competencies at UPT SMPN Garaupa No. 13 Selayar Islands. This research is a qualitative study with a descriptive approach. The subjects in this study were supervisors, principals, MGMPS leaders, and 3 Integrated Social Studies teachers. Data collection techniques in this study used interviews, observation, and documentation while the data analysis techniques used included data reduction, data presentation, and conclusion drawing/verification. The results showed that the School Level Subject Teacher Conference (MGMPS) at UPT SMPN Garaupa No. 13 Selayar Islands has an important role in improving teachers' pedagogical and professional competencies. Through this forum, teachers gain a better understanding of the curriculum, improve their teaching skills and share knowledge through collaborative learning. MGMPS also introduces innovative learning methods and supports the mastery of teaching strategies that suit students' needs. Barriers such as limited resources, low teacher participation and difficulties in program planning are overcome with resource support, increased motivation and relevant mentoring. Other solutions include external collaboration for training, strategies to increase participation and technical support in curriculum planning. These efforts are expected to increase the effectiveness of MGMPS in developing teachers' competencies on an ongoing basis..